Percutaneous aortoiliac thromboendarterectomy with Inari ClotTriever system for chronic juxtarenal aortoiliac occlusion - Laurencia Villalba, MD, FRACS; Erin C. Saricilar, BMed, MD, MM, MS; Nicolas J. Mouawad, MD, MPH, MBA, FSVS, FACS, FRCS, RPVI (Journal of Vascular Surgery Cases and Innovative Techniques)
This case describes a percutaneous thromboendarterectomy using the Inari ClotTriever system to treat a chronic juxtarenal aortoiliac occlusion in a 55-year-old man with critical limb ischemia and a single kidney. The procedure was fast, safe, and effective with no complications. There was no need for balloon angioplasty or stenting. This case demonstrates the expanding indications for large bore thrombectomy devices offering minimally invasive options.